Teatro folk e sciamanesimo in Corea - Giovanni Azzaroni (Antropologia e Teatro)
The exact date of birth of Korean theater is uncertain, but its origins can be traced back to ancient ceremonies, folkloric rites, and shamanic rituals that date back more than two thousand years. Theatrical forms can likely be identified in civil rites, celebrated with dances, songs, and masks to worship the heavens and appease ancestral spirits. In Korean dances, various parts of the body are interconnected, delicate aesthetic gestures indicative of the dances that inspire them are displayed, and the upper body is emphasized. Scholars believe that Korean theater finds its greatest expression in danced ritual dramas, which, until the early 20th century, along with puppet theater, were appreciated by both urban and rural audiences. Today, Korean popular theater can be summarized in forty-one masked dramas, rites, and folkloric plays inspired by myths and popular tales.